Synthesis and Biological Properties of 2(5H)-Furanones Featuring Bromine Atoms on the Heterocyclic Ring and/or Brominated Substituents - Rossi, Renzo; Lessi, Marco; Manzini, Chiara; Marianetti, Giulia; Bellina, Fabio (Current Organic Chemistry, 2017)
This review deals with the synthesis of unnatural and natural 2(5H)-furanone derivatives featuring bromine atoms on the heterocyclic ring and/or brominated substituents, which have been described in the literature since 1951 up to February 2016. The review has been organized on the basis of six classes of brominated furanone derivatives that were synthesized: i) 2(5H)-furanone derivatives with one bromine atom on the heterocyclic ring; ii) 2(5H)-furanone derivatives with two bromine atoms on the heterocyclic ring; iii) 2(5H)-furanone derivatives featuring one bromine atom on the heterocyclic ring and monobrominated substituents; iv) 2(5H)- furanone derivatives featuring one bromine atom on the heterocyclic ring and dibrominated substituents; v) 2(5H)-furanone derivatives with monobrominated substituents; and vi) 2(5H)-furanones featuring dibrominated substituents. Where possible, experimental details of the syntheses have been reported. Furthermore, the biological properties of the target compounds, including their mutagenic, cytotoxic, enzymatic, anti-inflammatory and photosynthetic inhibitory activities have been summarized, paying particular attention on the compounds that have demonstrated antimicrobial properties via inhibition of quorum sensing and biofilm formation.
Keywords: antimicrobials